Respostas
respondido por:
1
x² + 10x + 25 = 0
x² + 10x + 5² = 0
(x + 5)² = 0
x + 5 = 0
x = -5
x² - 3x + 10 = 0
∆ = -31*
x = 3 ± √-31 / 2
*Sem solução!
x² - 2x + 1 = 0
x² - 2x + 1² = 0
(x - 1)² = 0
x - 1 = 0
x = 1
Talvez seu professor não entenda os métodos que uso para resolução, mas estão corretos!
x² + 10x + 5² = 0
(x + 5)² = 0
x + 5 = 0
x = -5
x² - 3x + 10 = 0
∆ = -31*
x = 3 ± √-31 / 2
*Sem solução!
x² - 2x + 1 = 0
x² - 2x + 1² = 0
(x - 1)² = 0
x - 1 = 0
x = 1
Talvez seu professor não entenda os métodos que uso para resolução, mas estão corretos!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás